2019
DOI: 10.3904/kjim.2017.284
|View full text |Cite
|
Sign up to set email alerts
|

Association between blood pressure, inflammation and spirometry parameters in chronic obstructive pulmonary disease

Abstract: Background/AimsMany systems including the cardiovascular system (ischemic heart diseases, heart failure, and hypertension) may act as comorbidities that can be seen during the course of chronic obstructive pulmonary disease (COPD). Comorbidities affect the severity and prognosis of COPD negatively. Nearly 25% of patients with COPD die due to cardiovascular diseases. In this study, we aimed to evaluate the relationship between the blood pressure, inflammation, hypoxia, hypercapnia, and the severity of airway ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
(42 reference statements)
0
8
0
1
Order By: Relevance
“…The accumulation of inflammatory cytokines may induce respiratory histopathologic changes. Increasing evidence supports that the presence of systemic inflammatory cytokines increased the risks of COPD and the comorbidities occurrence (7). Circulatory proinflammatory cytokine CRP is an important marker of systemic chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of inflammatory cytokines may induce respiratory histopathologic changes. Increasing evidence supports that the presence of systemic inflammatory cytokines increased the risks of COPD and the comorbidities occurrence (7). Circulatory proinflammatory cytokine CRP is an important marker of systemic chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data have demonstrated that activated inflammatory cells and inflammatory cytokines lead to systemic inflammation, which is associated with extrarespiratory manifestations of COPD (5). C-reactive protein (CRP) and systemic inflammatory markers were increased in COPD patients (6,7). However, the potential molecular mechanism of inflammation-induced COPD is unclear.…”
mentioning
confidence: 99%
“…The systolic blood pressure (SBP) and diastolic blood pressure (DBP) and pulse rate significantly are different in COPD patients as compared to in the manage group. The only pathophysiology can understand its complications [ 69 ]. The red blood cell distribution width (RDW) values were significantly higher in COPD patients as compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Проте, можливий розвиток ХОЗЛ і на фоні раніше існуючої гіпертонічної хвороби або симптоматичної артеріальної гіпертензії. Кожна з цих нозологій значно змінює перебіг та наслідки цих захворювань [4].…”
Section: дана стаття є фрагментом ндр кафедри клінічної фармакологіїunclassified